Analysis of Nitrate, Phosphate, and Phytoplankton Abundance Content in Apar Waters Pariaman City West Sumatra - Adini Dwi Ratna Hafnizar; Syahril Nedi; Elizal Elizal (Jurnal Natur Indonesia, 2024)
Apar Beach is one of the tourist destinations in North Pariaman District, Pariaman City, West Sumatra. These tourism activities can affect water quality. In addition to anthropogenic activities, several factors can affect the quality of these waters, among the compounds contained in Apar waters, namely the content of nitrates, phosphates, and the abundance of phytoplankton. This study aimed to determine nitrate and phosphate content, how phytoplankton abundance, and the relationship between nitrate, phosphate, and phytoplankton abundance. The survey method was used in this study. The results of this study showed nitrate content at station I of 0.82 mg/L. Station II is 0.78 mg/L and station III is 0.90 mg/L. while the phosphate content at station I is 0.72 mg/L. station II is 0.71 mg / l and station III is 0.73 mg/L. The average phytoplankton abundance at station I was 249.99 ind/l. Station II is 288.88 ind/l, and station III is 327.77 ind/L. The relationship between nitrate and phosphate concentration with phytoplankton abundance is obtained value (R2) 0.215, which means nitrate and phosphate affect phytoplankton abundance by 21.5%. In comparison, 78.5% is influenced by other factors, while the correlation coefficient value (r) of 0.464 means that nitrate and phosphate concentration with phytoplankton abundance has a moderate relationship.